Réponses

  • Utilisateur Brainly
2014-10-24T13:23:53+02:00
1) 2 x a x (- 5) x b                 avec ab = 1,5
= 2 x (- 5) x 1,5
= - 10 x 1,5
= - 15

2)  (- 0.5) x (- a) x (- 6) x  b x (- 2)                 avec ab = 1,5 donc - ab = - 1,5
(- 0,5) x (- 6) x (- 2) x (- 1,5)
= 3 x 3
= 9
2014-10-24T13:29:12+02:00
1) 2 x a x (-5) x b
    -10 x ab
    -10 x 1,5
     -15

2) (-0,5) x (-a) x (-6) x b x (-2)
     -6 x (-ab)
     -6 x (-1,5)
       9

On calcule d'abord les chiffres et les lettres entre eux puis en remplace les lettre par le nombre indiqué.